Thermodynamic analysis of nitrate Adsorption onto spent mushroom substrate and granular activated carbon - Ainon Binti Md. Nor (School of Bioprocess Engineering, University Malaysia Perlis, 2017)
The removal of nitrate from water sources is important because the presence of nitrate can affect bad consequence on human health and environment. Adsorption using biomass adsorbent is one of suitable methods for nitrate removal. Spent mushroom substrate (SMS) is one of the agricultural by product that can be used as a low cost adsorbent for nitrate removal. This study was conducted on the thermodynamic analysis of nitrate adsorption onto SMS and Granular Activated Carbon (GAC). The batch adsorption experiments were conducted at various process parameters such as pH (3-11), initial concentration of nitrate (100-500mg/L), temperature (25-55C) and solid/liquid ratio (20-100 mg/L). The experimental data from the batch adsorption experiments were analyzed in order to find the value of equilibrium constant, KC. The thermodynamic parameter calculated from the KC constants was 0.0021 which was derived from the Langmuir isotherm for SMS while KC for GAC was 0.0081. The optimal selection of KC was strongly depends on the adsorption characteristics where the equilibrium data were actually located and the correlation coefficient of the Van't Hoff equation. It was observed that the increasing of initial nitrate concentration has resulted in the decreased of percentage of nitrate removal. The adsorption performance was decreased with increasing temperature. The pH near to the point of zero change (pHpzc) can increased the nitrate removal. Meanwhile, for the effect of solid/liquid ratio, the increasing in the amount of adsorbent have resulted the nitrate removal efficiency increase